Relacionamentos humanos mediados pelo computador: as experiências de intermautas cadastros no site de comunidades UOL K - DINIZ, Caetano da Providência Santos (Universidade Federal do Pará, 2014)
The community web sites have attracted a great number of people. They relate in distance to each other using resources such as the sending of mails and messages. These people also change information among themselves through the auto-description (profile) and the use of images, both free to the internet users public. The experience of having a personal web page in this kind of environment and the opportunity of relating with people through that result on the objective of this research which has been realized based on a qualitative methodology .There have been interviewed 16 internet users of UOL K network that belongs to UOL (online universe) that is considered the main vestibule of content and an access paid-supplier of internet in Brazil as well. The results analysis has pointed the following features: The web site makes possible the establishment of new contacts as well as the maintenance of old contacts. There is a trend to make new contacts. The written language is used such for communication as for a reflection about yourself. The anonymity is favored by the distant communication but it causes distrust of disappointing someone. The exercises are seen as real even they happen in a virtual atmosphere. “Being online” can be pleasant but it does not mean that we have to come off from the offline world. The communities’ membership is frequent and it is based on its common objectives. Thanks to the web sites tools, the use of photo is a link between the synchronous communication (chat) and the asynchronous communication (UOL K).There is an emphasis given to the sexuality and, consequently, the internet users find themselves needed to see and relativize their concepts like close and far, public and private, offline and online.It´s concluded that, even the users don’t use to set face - to –face dates, they are able to relate virtually to each other as a real situation, change affection, state links and keep an online life which communication finds its own way that maybe there will be not another goal except being online.